Psychological and Pedagogical Support in the Adaptation of a Gifted Child to School - Eroshina D. A. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
it is noted that gifted children have particular qualities which must be taken into account while working with them. This fact leads to the specifics of child’s adaptation to school. It is pointed out that the adaptation of a gifted child to school must be accompanied by the teacher-psychologist, who organizes psychological and pedagogical support in the unity of all its components: diagnosis, consulting, developing and correcting.
Keywords: психолого-педагогическое сопровождение; gifted child; psychological and pedagogical support; адаптация к школе; ребенок с одаренностью; adaptation to school